Fire in the canyon : religion, migration, and the Mexican dream - Sarat, Leah (NYU Press, 2013)
"The canyon in central Mexico was ablaze with torches as hundreds of people filed in. So palpable was their shared shock and grief, they later said, that neither pastor nor priest was needed. The event was a memorial service for one of their own who had died during an attempted border passage. Months later a survivor emerged from a coma to tell his story. The accident had provoked a near-death encounter with God that prompted his conversion to Pentecostalism. Today, over half of the local residents of El Alberto, a town in central Mexico, are Pentecostal. Submitting themselves to the authority of a God for whom there are no borders, these Pentecostals today both embrace migration as their right while also praying that their "Mexican Dream"--the dream of a Mexican future with ample employment for all--will one day become a reality. Fire in the Canyon provides one of the first in-depth looks at the dynamic relationship between religion, migration, and ethnicity across the U.S.-Mexican border. Faced with the choice between life-threatening danger at the border and life-sapping poverty in Mexico, residents of El Alberto are drawing on both their religion and their indigenous heritage to demand not only the right to migrate, but also the right to stay home. If we wish to understand people's migration decisions, Sarat argues, we must take religion seriously. It is through religion that people formulate their ideas about life, death, and the limits of government authority. Leah Sarat is Assistant Professor of Religion at Arizona State University"--